A case study of cash cropping in Nepal: poverty alleviation or inequity? - Brown, S.; Kennedy, G. (Springer, 2005)
Agricultural commercialization as a mechanism to alleviate rural poverty raises concerns about small land-holders, non-adopters, and inequity in the distribution of benefits within transforming economies. Farm gross margins were calculated to assess the economic status and impact of cash cropping on the economic well-being of agrarian households in the Mid-hills of Nepal. On an individual crop basis, tomatoes and potatoes were the most profitable. On a per farm basis, 50 of the households with positive farm gross margins grew at least one vegetable crop, while only 25 of households with negative farm gross margins included vegetable crops in their rotation. Farmers have been hesitant to produce primarily for the market given the rudimentary infrastructure and high variability in prices. Farmers reported selling more crops, but when corrected for inflation, gross revenues declined over time. The costs and benefits of developing markets have been unevenly distributed with small holders unable to capitalize on market opportunities, and wealthier farmers engaging in input intensive cash cropping. Farms growing vegetables had an average gross margin of US$137 per year compared to US$12 per year for farms growing only staple crops. However, the area under production is small, and while vegetable production is likely to continue increasing, sensitivity analysis and scenarios suggest high variability and limited short-term impact on poverty alleviation.